PERENCANAAN BANGUNAN PENAHAN SEDIMEN (CHECKDAM III) DI DAERAH ALIRAN SUNGAI CILIMAN DESA PARAKANLIMA KECAMATAN CIRINTEN KABUPATEN LEBAK - Gunawan Noor; Euis Amelia; Dimas Bayu (LPPM, 2019)
The river is a source of water that holds and flows water and material that it carries from upstream. The problem that often occurs in upstream areas is erosion problems which cause sedimentation. The objectives of this study are: to determine the amount of sediment rate (Qs) and to find out the full time of the water river checkpoint. So it needs to be reviewed by analyzing the stability of sediment-retaining weirs using a flood period of fifty years (O50), with a design debit of 255.694 m3 / second, this study was also conducted to determine whether the stability of sediment-retaining weirs is safe against forces with flood discharge (Q25), with a design debit of 237.692 m3 / second. The style calculated by himself is gravity, earthquake force, uplift pressure, pressure on water. The weir stability analysis that is taken into account is the dimensions of the weir safe against eccentricity, soil carrying capacity, bolster force, shear force, and force acting on normal water level conditions and flood water levels. The location of this study was carried out in the Watershed (DAS) Air Ciliman Cirinten District, Lebak Regency.